2011
DOI: 10.1016/j.brainres.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The integration of disparity, shading and motion parallax cues for depth perception in humans and monkeys

Abstract: A visual stimulus display was created that enabled us to examine how effectively the three depth cues of disparity, motion parallax and shading can be integrated in humans and monkeys. The display was designed to allow us to present these three depth cues separately and in various combinations. Depth was processed most effectively and most rapidly when all three cues were presented together indicating that these separate cues are integrated at yet unknown sites in the brain. Testing in humans and monkeys yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The latency differences between paired and single presentations were significant beyond the 0.005 level. These findings are in agreement with previous work we have reported showing that in normal subjects when three depth cues, disparity, parallax and shading are presented in various combinations, the combined presentation of all three cues yields significantly faster reaction times than the presentation of single or paired cues [24]. That reaction times are faster when both disparity and motion parallax cues are presented than when these cues are shown singly, has been established in our previously published studies carried out in normal human and monkey subjects, indicating that the brain can advantageously integrate these cues [23,24].…”
Section: Stereopsis and Motion Parallax Testssupporting
confidence: 93%
See 1 more Smart Citation
“…The latency differences between paired and single presentations were significant beyond the 0.005 level. These findings are in agreement with previous work we have reported showing that in normal subjects when three depth cues, disparity, parallax and shading are presented in various combinations, the combined presentation of all three cues yields significantly faster reaction times than the presentation of single or paired cues [24]. That reaction times are faster when both disparity and motion parallax cues are presented than when these cues are shown singly, has been established in our previously published studies carried out in normal human and monkey subjects, indicating that the brain can advantageously integrate these cues [23,24].…”
Section: Stereopsis and Motion Parallax Testssupporting
confidence: 93%
“…The use of randomdot stereograms, as developed by Julesz [27], is outstanding for this purpose as it can isolate cues to selectively activate mechanisms that process only disparity or only motion parallax [28]. We have published several papers studying normal humans as well as monkeys using this stereopsis and motion parallax test [23,24,26,29].…”
Section: Discussionmentioning
confidence: 99%
“…1 In other studies on combining disparity and shading, it has been shown that reliability improves as more information is provided, but judgments do not necessarily become more accurate (Vuong, Domini et al, 2006). Judgments of depth may also be achieved more quickly when shading and disparity are combined (Schiller, Slocum et al, 2011;Zhang, Weiner et al, 2007). Mingolla and Todd (1986) found that observers underestimated surface curvature in non-stereo displays compared with stereo viewing.…”
Section: Combining Disparity and Shading For Depth Perceptionmentioning
confidence: 99%
“…Finally, Zhang et al (2007), using an oddity task, have provided evidence that monkeys can also perceive 3D shape from shading, although performance was poorer in monkeys than in humans. Thus the available evidence suggests macaque monkeys process 3D shape, particularly from motion or disparity, and combine cues (Schiller et al 2011) in ways similar to humans. Disparity + texture (n = 56)…”
Section: Perception Of 3d Shapementioning
confidence: 99%